Building Communities of Philanthropy in Higher Education: Contextual Influences - McAlexander,Jim; Koenig,Hal (International Journal of Nonprofit and Voluntary Sector Marketing, 2012)
In this era of constrained and declining economic resources, institutions of higher education are turning to advancement professionals to identify and cultivate the financial resources that are becoming an increasing and larger portion of the fundamental funding of the institution. In this high stakes arena, advancement professionals have a need for the tools that can assist them in cultivating philanthropic relationships more effectively and efficiently. To that purpose, this research empirically explores ways in which the brand community construct can be adapted to philanthropic intent for non-profit organizations to aid in the cultivation process. This paper presents the results of a survey of college alumni drawn from a commercially provided on-line panel, and examines the potential impact that institutional size may have upon the relationships of an alumni brand community and the community’s expressed willingness to offer financial donations to the alma mater. From a theoretic perspective, this paper reveals that brand community is a significant contributor to this expression of philanthropic intent across universities of differing size. As a practical consideration, our findings produce additional evidence to affirm the notion that brand community is a robust construct that can be of value to development professionals who seek to build financial support for both small and large universities.
Keywords: Marketing

Building the Relationships of Brand Community in Higher Education: A Strategic Framework for University Advancement - McAlexander,Jim; Koenig,Hal; Schouten ,John W. (International Journal of Educational Advancement, 2006)
Loyal alumni are a mainstay of financial support for many universities. This empirical study of university alumni situates the emerging theory of brand community within the world of university development and advancement. The study measures key relationships that one would expect to find in a healthy university brand community. Most importantly, this research demonstrates the powerful contribution that understanding and managing brand community can make to those interested in the advancement of higher education. We find that integration within a university brand community explains important loyalty-related behaviors such as future donations to the university and the purchase and display of university logo merchandise.
Keywords: Marketing

Brand Community in Higher Education: A Framework for Understanding and Building Loyalty - Koenig,Hal; McAlexander,Jim; Schouten,John W (Symposium for the Marketing of Higher Education, 2005)
Keywords: Marketing

Building a University Brand Community: The Long-Term Impact of Shared Experiences - McAlexander,Jim; Koenig,Hal; Schouten ,John W. (Journal of Marketing for Higher Education, 2004)
Relationship marketing has made its way into the practices of university administrations. With it have also arrived many problems associated with the aggressive use of CRM technologies. One particularly effective and healthy approach to relationship marketing in higher education is to treat the university, with all of its stakeholders, as a brand community, and to pursue policies and programs to strengthen the relationships that define the community. With this paper, we examine an important class of relationship often neglected in the CRM literature, i.e., the relationships among the customers who support the brand and who ultimately give it its meaning and vitality. Specifically, we explore how the nature of relationships among students affects their long-term loyalty to a university. The results of a telephone survey of university alumni demonstrate the importance of certain types of university experiences on student relationships and, thereafter, on loyalty to their alma mater and their intentions to support the university in the future.
Keywords: Marketing

Building the Relationships of Brand Community in a Service Setting - Koenig,Hal; McAlexander,Jim (American Marketing Association Winter Educators' Conference, 2003)
Keywords: Marketing

Building Brand Community - McAlexander,Jim; Schouten ,John; Koenig,Hal (Journal of Marketing, 2002)
Drawing from ethnographic and quantitative work with owners of Jeep and Harley-Davidson vehicles, the authors examine the phenomenon of brand community as a potential basis for sustainable competitive advantage. The authors develop an expanded conceptualization of brand community and test its usefulness in both theory and practice. A brand community from a customer-experiential perspective is a fabric of relationships in which the customer is centrally situated. Crucial components of the brand community are customers' relationships with the brand, with the firm, with the product in use, and with fellow customers. The relationships that form a brand community develop in contexts that are dynamic and subject to marketing influence. Variables such as geographic concentration, richness of social context, duration of contact, and memberships in multiple or overlapping communities all mediate the experience of community. In this article, the authors examine the influence of brandfeststhat is, programs strategically designed to enhance customer experience with the brandon the many component relationships of a brand community. The results demonstrate that marketers can strengthen brand communities by facilitating shared customer experiences. Finally, this work yields a new and richer conceptualization of customer loyalty as integration in a brand community. According to the analysis, a customer's loyalty to a brand consists of the cumulative and holistic effect of all the relationships the customer experiences as a member of a brand community.
Keywords: Marketing

The Bases of Marketing Channel Power: A Comparison of Alternative Measures - Koenig,Hal; Brown ,James R.; Johnson,Jean L. (AMA Summer Educators' Conference, 1986)
Keywords: Marketing

The Bases of Marketing Channel Power: An Exploration and Confirmation of Their Underlying Dimensions - Koenig,Hal; Johnson,Jean L.; Brown,James R. (AMA Summer Educators' Conference, 1985)
Keywords: Marketing

The Bases of Power: Their Effect Upon Retailer's Perceptions of Uncertainty - Koenig,Hal; Kroeten ,Terrence T.; Brown,James R. (AMA Summer Educators' Conference, 1984)
Keywords: Marketing